Peran Dinas Pendidikan Dalam Wajib Belajar di Tinjau Menurut Fiqh Siyasah - Alawiyah, Rafida (Jurnal El-Thawalib, 2022)
This research  discusses the Role of the Education   Office in the Compulsory Education Program  in  the New Village of Batahan District, West  Pasaman Regency, this research was motivated by the large number of children who  Drop out of  school and  prefer to work while judging from the age of children aged 7-18 years should be eligible to sit in  the pendidiment and complete their education until produce diplomas from elementary, junior high and high school so as to cause implementation that is not in accordance with existing  rules.  This type of research  is field research (Field Researche)  using qualitative descriptive analysis methods, this method of  collecting data  collection is by interview and  documentation.  The parties studied are   the West Pasaman Regency Education Office, The Community and Children who dropped out of school in  the NewVillage of  West Pasaman Regency. The results of the study that said that the Role of the Education  Officeinthe Compulsory Education Program  in  the NewVillage of Batahan District of West  Pasaman Regencyhave been carried out.  This is seen from the form of implementation that has been implemented by the Education  Office by  socializing  to schools, UPTD and the community, but not yet maximal and still Many children drop out of school and prefer to work  and  do not produce a diploma.